Pengaruh Laba Kotor, Laba Operasi dan Laba Bersih dalam Memprediksi Arus Kas di Masa Mendatang Pada Perusahaan Manufaktur - Desrawani Situmeang (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This study aims to provide empirical evidence on gross profit, operating profit and net income by testing each variable to predict cash flow. The research subjects are manufacturing companies listed on the Indonesia Stock Exchange in 2019, using Indonesian rupiah currency units in their financial statements and companies that do not experience losses by disclosing and providing the necessary data. The method of selecting the subject of this research is to deliberately take a sample of 45 companies. The analysis model used in this research is multiple linear regression analysis model with the help of Eviews 10 program. The results showed that gross profit has a significant positive effect on cash flow, while operating profit and net profit have no significant effect on cash flow. However, gross profit, operating profit, and net profit also have the ability to predict cash flow. Based on the results of the determinant test, sufficient coefficients are calculated so that the selected model can be used as a future cash flow forecasting model.